PENGARUH LINGKUNGAN KERJA, DAN PENGARUH KEPEMIMPINAN, SERTA INSENTIF TERHADAP KINERJA KARYAWAN RSUD CARUBAN KAB MADIUN: PENGARUH LINGKUNGAN KERJA, DAN PENGARUH KEPEMIMPINAN, SERTA INSENTIF TERHADAP KINERJA KARYAWAN RSUD CARUBAN KAB MADIUN - Awaluddin, Sri Prilmayanti; Maulidah, Fitria (Program Pasca Sarjana IBK Nitro, 2024)
The research is intended to analyze the influence of the work environment, leadership and incentives on employee performance at Caruban Hospital, Madiun Regency. A conducive work environment, effective leadership and appropriate incentives are important factors in creating optimal performance in the health services sector. A quantitative approach was applied through the implementation of a survey method, where data collection was carried out using a questionnaire aimed at Caruban Regional Hospital employees. Research findings have revealed that the work environment has a significant influence on employee performance levels, with the greatest contribution coming from physical comfort and positive interpersonal relationships. A leadership style that involves direct participation and activeness has a significant influence on performance achievements, especially in the aspects of communication and decision making. In addition, incentives, both financial and non-financial, have been proven to increase employee motivation and productivity. This research provides practical recommendations for the management of RSUD Caruban to optimize the work environment, develop an effective leadership style, and improve the incentive system to improve overall employee performance.